Performance of a state farmers’ organization on broiler supply chain based on environmental life cycle costing in Johor, Malaysia - Samsuddin, Nur Syahirah (2018)
Malaysia currently had achieved full self-sufficiency level in poultry industry. However, the increase in demand for poultry meat due to boost in population and demand for nutritional foods had provided greater pressure towards poultry industry efficiency. Hence, the poultry production sector had been expanded and enlarged to cope with the unexpected demand by Malaysian for poultry products. This situation triggers the existence of integrated system called broiler chicken meat supply chain. Therefore, this study aims to investigate the performance of broiler chicken meat supply chain with the inclusions of environmental cost for sustainable production and environment. The methods employed in this study are based on ELCC general framework which consisted of three stages: 1) goal and scope definition, 2) information gathering 3) identification of significant hotspot. However, the sensitivity analysis that follows attempt to evaluate changes in key variables. The primary data collected through face to face interview consisted of 1 breeder, 30 producers and 1 processor in Johor. The cost structure generated for operational expenditure show that the feed cost had been the major expenditure in breeder and contract farm levels. Meanwhile, for the processing plant, farm gate chicken had become the major operational expense incurred. The environmental cost for the ecosystem was the significant environmental cost hotspot and had been traced throughout the three stages of broiler chicken meat production. After the inclusion of environmental cost in the base line financial model, the performance evaluation results show that a small decline in NPV and IRR value occurred. However, the NPV and IRR value for those three stages are positive, even though the environmental cost was included in the cost of production. Next, the sensitivity analysis was conducted and the results showed that when different scenarios of environmental cost had been included at 5%, 10% and 15%, the NPV value are still positive but the value decline proportionately. In summary the three stages of broiler chicken meat supply chain are feasible and viable to be implemented even after the environmental cost had been included in the cost of production, and hence, the study was successful in modelling environmental cost in the life cycle costing of broiler supply chain.